R&d subsidy and import substitution: Growing in the shadow of protection - Gustavo de Souza (Federal Reserve Bank of Chicago, 2023)
I study the effect of an innovation subsidy on the growth of firms in a developing country. Using administrative microdata for Brazil and difference-in-differences, I find that innovation subsidies drive firm growth by facilitating firm entry into high-tariff markets with domestically produced, lower-quality versions of foreign goods. After receiving an innovation subsidy, firms issue more patents, expand their workforce, and diversify their product line. However, these patents receive minimal citations, while also heavily citing foreign patents, and are primarily associated with higher tariff patent classes, highlighting that these innovations build on foreign technologies currently facing high import tariffs in Brazil. Overall, these findings indicate the efficacy of innovation subsidies in promoting both growth and import substitution in developing countries.
Keywords: O3; O14; O25; 330; R&D subsidy; industrial policy; industrial development